Compulsive Internet use and relations between social connectedness, and introversion. (July 2015) - McIntyre, Erica; Wiener, Karl K.K.; Saliba, Anthony J.
Highlights: People with poor social connectedness have a greater risk of developing compulsive Internet use. More introverted people appear to be more vulnerable to compulsive Internet use. Using the Internet can become problematic and lead to poor social connectedness. Compulsive Internet Use Scale is a reliable and valid scale in a sample of students. Abstract: This study aims to further understand factors involved in compulsive Internet use, with specific focus on the relation between social connectedness, the trait introversion, and compulsive Internet use. While Internet use can enhance social connectedness, compulsive Internet use has been associated with poor social connectedness. The factors that make a person vulnerable to compulsive Internet use and its negative effects remain unclear. The personality trait introversion has been associated with poor social connectedness, and there is disagreement on whether or not social interaction on the Internet is beneficial for people high in this trait. Australian university students ( N  = 168) participated in an online survey. Standardised scales were used to measure social connectedness, introversion, and compulsive Internet use. Results show that introverted adults report more compulsive Internet use symptoms than extroverts. In addition, introversion partially mediated the relation between compulsive Internet use and social connectedness. The results raise questions for future research into factors involved in the development of compulsive Internet use and its effect on social connectedness, especially in those who are introverted.